MENAKSIR RISIKO SISTEMATIK DENGAN MENGGUNAKAN PENDEKATAN RETURN INTERVAL DAN ESTIMATION PERIOD DI BURSA EFEK JAKARTA PERIODE TAHUN 1998-2001 - Aribowo, Fajar (Jurnal Manajemen dan Keuangan, 2010)
An investor or investment manager, in making a decision, has to pay attention on to two main factors, i.e., the level of expected return and risk. There are two risks of investment, systematic risk and unsystematic risk. According to Ariff and Johnson (1990), risk that cannot be diversified (systematic risk) is risk relevant with investment decision.In considering the systematic risk, known as beta (ï¢), an investor or investment manager has to determine the use of return interval and estimation period in estimating it, in this study was to prove whether the uses of returns (daily, weekly, or monthly returns) and the etimation period, which can produce optimal beta.This study proves the use of daily returns in calculating the systematic risk in the capital markets will be able to produce optimal beta which helped minimize losses on investments by delivering the proper systematic risk assessment.Keyword: Systematic risk, return interval and estimation period.